The Impact of Institutional, Strategic, and Structural Constraints, Along With Management Competencies on Black-Owned SMMEs Performance: a Structural Equation Modelling Approach - Tlhagale, Felicity Kgomotso; Ndou, Adam (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: The worldwide discussion focused on investigating the impact of institutional constraints, management capabilities, and both structural and strategic constraints on performance outcomes of small, medium, and micro enterprises (SMMEs).Objective: This study aims to enhance and widen the analysis by investigating how institutional, strategic, and structural constraints, along with management capabilities, affect the performance measures of Black-owned SMMEs, intending to provide a more thorough and expansive analysisDesign/methodology/approach: A quantitative analysis approach was employed, using a structural equation model to examine the interconnections among various factors, including financial, informational, and human capabilities in relation to management capabilities, as well as financial and organisational development in relation to performance. A total of 544 small businesses owned by Black individuals in South Africa participated in the study.Results: The results demonstrate a negative correlation between institutional constraints and business performance (H1), along with a similar negative relationship between strategic and structural constraints and performance (H2). In contrast, the anticipated positive link between management competencies and performance (H3) was not confirmed. These findings highlight the necessity for proactive measures to transform regulatory settings and improve organisational structures.Conclusion: This study tackles a crucial void in the existing literature by exploring the connections among organisational limitations, operational and strategic challenges, management skills, and entrepreneurial success. There is an urgent need for collaborative initiatives among policymakers, business development agencies, and stakeholders to promote entrepreneurship, improve management skills, and bolster organisational frameworks. Through these interventions, Black-owned SMMEs will thrive, generate employment, inspire innovation, and aid in overall economic and social progress.Originality/value: The present research is the initial exploration into the detrimental impact of institutional, strategic, and structural limitations, along with management capacities, on the entrepreneurial performance of SMMEs within South African contexts. Keywords: black-owned smmes, business performance, institutional constraints, management competencies, structural barriers